STATISTICAL APPROACH TO ESTIMATING OF EDUCATIONAL PROCESSABILITY - Луханін, І. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article presents a model of analysis, allowing on the base of statistical methods to define the degree of educational processability. Methods conform to the requirements of ISO 9001-2009 "Quality management systems " and allows to manage efficiency of technologies of teaching and control of knowledge